Empirical study of Jump Diffusion warrant pricing model on the Stock Exchange of Singapore. - Chiam, Fong Sin. (2009)
Warrants have become a popular financial instrument for companies raising funds in the local capital markets. When considering investments in warrants, financial analysts and brokers commonly apply a standard call option model to the underlying stock. The pricing of warrants is a natural extension of option pricing models because of the many similarities between call options and warrants.